2001
DOI: 10.1007/s004180000221
|View full text |Cite
|
Sign up to set email alerts
|

Subcellular localization of Dp71 dystrophin isoforms in cultured hippocampal neurons and forebrain astrocytes

Abstract: It has been suggested that the absence or altered structure of Dp71, a C-terminal dystrophin gene encoded protein, is responsible for mental alterations observed in about 30% of Duchenne muscular dystrophy patients. Most of these patients have premature translational termination or point mutations at the C-terminal domain of this gene. In brain, Dp71 is the major protein product of the dystrophin gene. To determine the function of Dp71 isoforms in this organ, it is important to document their presence and intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 36 publications
1
17
0
Order By: Relevance
“…Thus, the clustered and polarized distribution of Kir4.1 channels may play a analogous role in astrocytes in brain as that of Müller cells in retina. Relevant to our findings, Dp71 is also expressed in astrocytes in brain (Aleman et al, 2001). Marked neurological dysfunctions for the mouse line mdx 3Cv has not been reported, but it is likely that a perturbation in the potassium buffering function in brain would only manifest under conditions of high neuronal activity.…”
Section: Discussionsupporting
confidence: 89%
“…Thus, the clustered and polarized distribution of Kir4.1 channels may play a analogous role in astrocytes in brain as that of Müller cells in retina. Relevant to our findings, Dp71 is also expressed in astrocytes in brain (Aleman et al, 2001). Marked neurological dysfunctions for the mouse line mdx 3Cv has not been reported, but it is likely that a perturbation in the potassium buffering function in brain would only manifest under conditions of high neuronal activity.…”
Section: Discussionsupporting
confidence: 89%
“…Neuropathological studies have demonstrated that dystrophin isoforms are missing from hippocampal areas. 22,23 Additionally, hippocampal brain slices from the mdx mouse (a model for DMD) have been shown to have reduced functional capacity in some situations. 24 Vailliend et al 25 have offered evidence that longterm potentiation associated with learning is disrupted in the mdx mouse, affecting memory consolidation.…”
Section: Discussionmentioning
confidence: 99%
“…Dystrophin 71 (Dp71), a membrane-associated cytoskeletal protein and one of the smaller Duchenne muscular dystrophy (DMD) gene products that is the core of the Dystrophin-Associated Protein (DAP) complex, links the intracellular actin cytoskeleton to the extracellular matrix. Studies on nervous tissue support the potential involvement of Dp71 in neuronal and glial cell functions (Aleman et al, 2001;Claudepierre et al, 2000;Dalloz et al, 2003;Daoud et al, 2009;Fort et al, 2008). Dp71 mRNA and protein have been shown to be expressed in different brain structures and cell types, including perivascular astrocytes, neurons in the hippocampus and olfactory bulb, cultured hippocampal neurons and forebrain astrocytes, and postsynaptic densities in vivo.…”
Section: Introductionmentioning
confidence: 94%